Nicotine Dependence Level and Sleep Quality in Patients Attending the Smoking Cessation Clinic - Yasin OBA; Özge BÖRKLÜ DOĞAN; Akın DAYAN (Bezmiâlem Science, 2025)
Objective: In our study, the aim is to investigate the impact of nicotine dependence level, smoking habits, and the desire to quit smoking on sleep quality, as well as their relationship with anxiety and depression levels. Methods: The study is a prospective case control research. Two hundred twenty-eight individuals who were admitted to family medicine and smoking cessation clinics (SCC) were included in the study, forming three different groups: those who smoked and visited the SCC, those who smoked, and those who did not smoke. Participants were administered Fagerstrom Nicotine Dependence Test, Pittsburgh Sleep Quality Index (PSQI), and Hospital Anxiety and Depression Scale. Results: In our study, the PSQI score of patients who wished to quit smoking and were admitted to the SCC was 5.29, while the PSQI score of other smokers was 4.58, and the PSQI score of non-smokers was 4.54. Although the PSQI scores of patients who were admitted to the SCC were higher, this wasn’t statistically significant (p=0.479). Statistically significant results were found regarding anxiety and depression levels between those who were admitted to the SCC and the other groups (p<0.001, p=0.015). The dependence level of the group smoking and visiting the SCC was significantly higher than that of the other group of smokers (p<0.001). Conclusion: Anxiety, depression, physical activity, and nocturnal eating are factors associated with sleep quality. Individuals who visit the SCC have higher scores for cigarette addiction, anxiety, depression, and questioning and treating their symptoms in this direction will be beneficial for the patient’s sleep pattern.